Vestibular Schwannoma in the Precision Medicine Era: An Updated Narrative Review of Molecular Insights, Imaging Biomarkers, and Evolving Management Strategies - Flavio Donnini; Giovanni Rubino; Giuseppe Battaglia; Pierpaolo Pastina; Marta Vannini; Tommaso Carfagno; Salvatore Chibbaro; Paolo Tini (The Journal of International Advanced Otology, 2026)
Vestibular schwannoma (VS) care is increasingly shaped by molecular and imaging advances that complement conventional size- and symptom-based decision-making. Recent multi-omic studies, including single-cell and spatial transcriptomics and methylation profiling, reveal biologically distinct Schwann cell states and microenvironmental programs that may help explain heterogeneous growth, hearing decline, and treatment response. In parallel, quantitative magnetic resonance imaging, radiomics, and early radiogenomic efforts are moving toward standardized, Image Biomarker Standardisation Initiative–compliant pipelines and automated segmentation, enabling more reproducible risk models. Clinically, prospective comparative evidence (e.g., Vestibular schwannoma: Radiosurgery or Expectation and Vestibular Schwannoma International Study of Active Surveillance has refined the observation vs. upfront radiosurgery debate for small-to-medium tumors, while contemporary planning emphasizes cochlear sparing to maximize hearing preservation. Targeted systemic therapy remains mainly relevant for NF2-related disease, with bevacizumab as proof of concept and multiple pathway-directed agents under evaluation. This narrative review synthesizes these developments and outlines a practical framework to integrate biology and imaging biomarkers into individualized surveillance and treatment selection, while highlighting limitations and priorities for multicenter validation.